Determination of some biochemical parameters in erythrocytes and serum of patients with prostate cancer related to lipid peroxidation (Journal of the College of Basic Education, 2023)
The aim of this study is to assess some biochemical parameters related to oxidative stress in erythrocytes and serum of patients with prostate cancer. Glutathione - S – transferase (GST) , glutathione peroxidase (GPx) and Xanthine oxidase (XO) activities was measured in erythrocytes , malondialdehyde( MDA), High density lipoprotien cholesterol (HDLc) , Low density lipiprotiens (LDLc) and selenium (Se) levels was measured in serum . Patients divided into two groups of men suffering from prostate cancer:- group A included (25) men suffering from this disease a period (1-2) years. Group B consisted of 25 patients suffering from this disease a period (2-4) years. Patients groups were compared with (25) healthy individual as a control group. Results have suggested that (GST) , (GPx) and (XO) activities were elevated in group (A) when compared to normal control. [ P<0.001 for (GST) , (GPx) and , (XO) ] , but then were decreased for group B [ P<0.01 for (GST) , (GPx) and , (XO) ]. Malondialdehyde ( MDA) level was increased in group A P<0.01 and this increasing was continued in group B P<0.001 .High density lipoprotiens (HDLc) level was decreased in group A P<0.01 and this decreasing was continued in group B P<0.001 while low density lipoprotiens (LDLc) level was increased in group (A) P<0.01 and this elevation was continued in group (B) P<0.001. Selenium (Se) was decreased in group (A) P<0.01 compared to healthy control, this decreasing was also continued in group (B) P<0.001.